Inclusive value chains: Pastoralism, pathways to prosperity - Jameel Observatory for Food Security Early Action (International Livestock Research Institute, 2024)
This poster was supervised by Tahira Mohamed and produced from a 'photovoice' project with young pastoralists in Kenya's camel production chain